MENINGKATKAN PEMAHAMAN PESERTA DIDIK TERHADAP LAYANAN BK DENGAN MENGGUNAKAN VIDEO TIKTOK DI SMK NEGERI 4 PALANGKA RAYA - zikraiyah, zikraiyah (Universitas Palangka Raya, 2021)
Guidance and Counseling (BK) services in schools aim to prepare students psychologically to optimally receive learning at school. The phenomenon that occurs at SMKN 4 Palangka Raya is that many students have a negative understanding of BK services in schools which causes students to be reluctant to take advantage of BK services. The purpose of this research is to increase students' understanding of Bk services in schools. The method used is a qualitative method with a guidance and counseling action research approach (PTBK). The steps of the research are carried out in cycles, each of which includes planning, action, observation and reflection steps. Data collection techniques using interviews, observations and questionnaires. The results of this study with 2 cycles showed that there was an increase in understanding of the percentage of the questionnaire by 37%. Prior to the research, the level of understanding of students was at 52%. After being given an intervention with information services using tiktok videos, there was an increase of 89%. In addition to the questionnaire, through observation, it was seen that students were active and enthusiastic in participating in information service activities with tiktok videos. Based on this explanation, the researcher concluded that information services using tiktok videos succeeded in increasing the understanding of students at SMK Negeri 4 Palangka Raya. Researchers hope that future researchers can make references and develop the use of tiktok videos, especially in improving students' understanding.